A prospective study of relationship of vascular pedicle width and cardiothoracic ratio in adult pulmonary oedema patients during treatment in icu - Ahmad Maulana, Siti Aishah (2011)
Introduction: Determination of intravascular volume status in critically ill patient is very important. Traditionally, invasive haemodynamic pressure measurements have been used to assess the volume status in this group of patients. However, the information available from vascular pedicle width (VPW) in portable supine chest radiographs are least costly and least invasive of determining volume status in critically ill patient. The true utility of VPW reflecting intravascular volume status seen in few studies from portable supine chest radiographs especially in monitoring patients who have volume overload and are receiving treatment. Objectives: To determine the relationship of vascular pedicle width (VPW), cardiothoracic ratio (CTR) and net fluid balance by using serial portable supine chest radiograph in adult pulmonary oedema patients during treatment in ICU in Hospital Universiti Sains Malaysia. Patients and Methods: A prospective study was done from Jun 2008 until Jun 2009 involving 51 patients who had been diagnosed to have pulmonary oedema in Intensive Care Unit (ICU) and Neuroscience ICU, Hospital Universiti Sains Malaysia. Serial supine portable chest radiographs were taken from day 1 of the onset of pulmonary oedema in ICU until day 3 consecutively. First chest radiograph was taken before starting treatment. Subsequent chest radiographs were taken about 24 hours apart. Three consecutive 24 hours net fluid balance data were taken from ICU monitoring chart according to the day of CXRs. Computed chest radiograph is used for evaluation of the VPW and CTR. The VPW and CTR were measured by researcher in separated occasion without clinical data related to patient available. Results: Fifty one patient involved in this study with the mean age of 54.43. Total of 39 patients (76.5%) received intravenous (IV) Frusemide and 12 patients (23.5%) received IV Frusemide in combination with dialysis as treatment of pulmonary oedema. There was a weak but not significant correlation between VPW and CTR in each day from day 1 (r1=0.10, p=0.34), day 2 (r2=-0.01, p=0.92) and day 3 (r3=0.02, p=0.91). Similar findings of a weak but not significant correlation was also seen between VPW and net fluid balance on day 1 (r1 =0.10, p=0.47), on day 2 (r2 = -0.05, p= 0.73) and on day 3 (r3 = - 0.05, p= 0.74). However by using paired t-test significant mean changes of VPW between day 1 to day 2 and between day 2 to day 3 (p<0.001). Significant mean changes of net fluid balance were also seen between day 1 to day 2 and between day 2 to day 3(p<0.001). No significant mean changes of CTR seen between day 1 to day 2 and between day 2 to day3 (p=0.58). In addition, there were daily reduction of the mean of VPW and net fluid balance in 3 days duration with IV Frusemide and combination treatment. However, no significant difference between both treatments with the mean of VPW (p=0.099) and net fluid balance (p=0.162) in 3 days period. Conclusion: This study showed that there was strong significant mean changes of VPW and net fluid balance between day 1 to day 2 as well as day 2 to day 3. However, no significant mean changes of CTR between day 1 to day 2 and day 2 to day 3.